Some Aspects of Indirect Taxes in Nepal - Shrestha, Prakash Kumar (NRB Economic Review, 2000)
Developing countries raise part of the vast financial resources required for their development needs from tax. Considering the limited scope of direct tax, revenue largely depends on indirect taxes like custom duty, sales tax and excise duty. Contribution of indirect taxes to total revenue has an erratic trend. Custom duty constitutes major source hence the revenue policy amounts virtually to import based. The distribution of incidence of indirect taxes has been found regressive. Buoyancy of components indirect taxes such as customs and sales tax is found greater than unity while that of excise duty is less than unity. In terms of GDP sales tax is found more buoyant.